RE EVALUASI TUGAS GURU PENDIDIKAN AGAMA BUDDHA DALAM PENGUASAAN DAN PENGEMBANGAN BAHAN AJAR DAN MODEL PENILAIAN - Hesti Sadtyadi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
This study aims to (1) know the mastery of the Buddhist education teacher on teachingmaterials, and the development of teaching materials. In addition in this study also aims (2) toknow the teacher's understanding in terms of the assessment used. This research is an evaluationresearch. That is an evaluation of the learning program of the Buddhist education teacher, interms of carrying out his duties, in the field of mastery and development of teaching materials,as well as his assessment model. Discrepency model is used to determine the level of conformitybetween the standards that have been determined in the program and the actual performance ofthe program. The results show that the mastery of the Buddhist education teacher on the teachingmaterial to be delivered is still imperfect and incomplete. The understanding of the teacher indeveloping teaching materials is still too far from the competencies that should be. The teacher'sunderstanding in terms of assessment is still imperfect, and the teacher's understanding of thedevelopment of assessment models that are in accordance with Buddhist education material, isstill in sufficient category, teachers are still limited in the use of older models, with standardmodels such as multiple choice instrument-based assessment models.